1998
DOI: 10.1021/ie9703346
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Poly(dimethylsiloxane)

Abstract: Poly(dimethylsiloxane) solutions are widely used in coating mixtures of many industrial coating processes. The flow of these solutions in and around the coating devices is strongly dependent on their rheological properties. This work presents a comprehensive experimental study of these properties. The tests were carried out for two poly(dimethylsiloxane), PDMS, solutions with vastly different viscosities, 1000 and 30 000 mPa·s. The measurements were taken on the RheoStress RS100 rheometer of Haake, over the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 4 publications
(3 reference statements)
0
22
1
3
Order By: Relevance
“…This result is confirmed by other studies (De-Deus et al 2007, Ozok et al 2008 in which Roekoseal Automix was found to have significantly the best sealing ability. Furthermore, polydimethylsiloxanes are known and widely used because of their low surface tension (Ghannam & Esmail 1998, Khorasani et al 2005. Contrary to the present study, Roekoseal Automix was found to have higher values and delayed wetting behaviour (Kontakiotis et al 2007) in comparison with a conventional epoxy-resin-and a zinc oxide-eugenol-based sealer.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This result is confirmed by other studies (De-Deus et al 2007, Ozok et al 2008 in which Roekoseal Automix was found to have significantly the best sealing ability. Furthermore, polydimethylsiloxanes are known and widely used because of their low surface tension (Ghannam & Esmail 1998, Khorasani et al 2005. Contrary to the present study, Roekoseal Automix was found to have higher values and delayed wetting behaviour (Kontakiotis et al 2007) in comparison with a conventional epoxy-resin-and a zinc oxide-eugenol-based sealer.…”
Section: Discussioncontrasting
confidence: 97%
“…) in which Roekoseal Automix was found to have significantly the best sealing ability. Furthermore, polydimethylsiloxanes are known and widely used because of their low surface tension (Ghannam & Esmail , Khorasani et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…three separate tests were performed to detect any possible deformation behavior for the concentrations of CMC of 5-8%. Yield stress was analyzed on the resulting plots of versus ␥, which are defined by conclusions from the literature [7][8][9]. Figure 7shows the yield stress response for all the concentrations used.…”
mentioning
confidence: 99%
“…A szilikonolajokat igen széles körben alkalmazzák az alap-és alkalmazott kutatástól kezdve a szerteágazó ipari felhasználásig [51,52]. A PDMS-t különleges reológiai viselkedése miatt gyakran használják a polimerkémiában és az anyagtudományokban: mátrix folyadékként (matrix fluid) szuszpenziókban [53][54][55][56] és kolloid diszperziókban, illetve polimer blendek komponenseként [58,59].…”
Section: áBra: a Poli-dimetil-sziloxán Térkitöltő Modelljének Egy Résunclassified
“…A korábbi poli-dimetil-sziloxán reológiai vizsgálatáról szóló cikkek többsége a 10 -50 Pas, vagy ez alatti dinamikai viszkozitású olajokról szól [52,63]. Igen kevés tanulmány foglalkozik sokkal magasabb viszkozitású szilikonolajokkal [64,65].…”
unclassified